Quality of life of chronic obstructive pulmonary disease and bronchial asthma patients in covid pandemic time in Delhi NCR - Roopam,; Ghotekar, L. H.; Talukdar, Tanmaya; Sharma, Sparsh; Islam, Sheikh Yasir (International Journal of Research in Medical Sciences, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is an irreversible airway obstruction disease with quality of life (QOL) being the major area for possible improvement. Asthma is a reversible airway obstruction also hampering the QOL of patients. This study aimed to assess the QOL of COPD and Bronchial Asthma patients and find the factors affecting it and relating it to clinical severity of the disease. Methods: It was a cross-sectional study in a hospital-based setting. SGRQ-C (Saint George’s respiratory questionnaire-C) was used to estimate the QOL scores, and spirometry was performed to assess the lung function. These scores were correlated with different Socio-demographic data that was recorded like age, sex, education, socioeconomic status, occupational etc. It was also correlated with clinical profile of patients consisting of duration of illness, smoking status, pack years of smoking, BMI etc. mMRC scale was used to assess dyspnoea. Results: Patients with asthma or COPD showed impaired health related quality of life (HRQOL). Increasing age, Duration of illness, dyspnoea severity, lower socioeconomic status and pack years of smoking showed strong positive correlation with the reduced QOL. Statistically significant negative correlation was seen between SGRQ-C QOL scores and FEV1 and FEV1/FVC ratio. No association between QOL scores and BMI or gender was observed. Conclusions: This study showed that Indian patients in Delhi NCR with COPD or Bronchial asthma had reduced HRQOL. Severity of lung function, increased duration of disease, smoking, increasing age and lower socioeconomic status impacted HRQOL negatively.